2016
DOI: 10.3892/or.2016.4579
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic cAMP responsive element binding protein 1 is overexpressed upon loss of tumor suppressive miR-10b-5p and miR-363-3p in renal cancer

Abstract: Renal cell carcinoma (RCC) is the most common kidney cancer in adults and has a poor prognosis. cAMP responsive element binding protein 1 (CREB1) is a proto‑oncogenic transcription factor involved in malignancies of various organs. However, its functional role(s) have not yet been elucidated in RCC. We investigated the expression pattern, function and regulation of CREB1 in RCC. CREB1 was overexpressed in the RCC tissues and cell lines. Downregulation of CREB1 inhibited RCC tumorigenesis by affecting cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…miR-10b is expressed in the kidneys of mice, dogs, and cats34. The role of miR-10b in KD is unknown, but a previous report suggested that upregulation of cAMP responsive element binding protein 1 by loss of miR-10b plays an important role in the tumorigenesis of renal cell carcinoma21. Furthermore, miR-10b is significantly downregulated in rejected allografts, and miR-10b inhibition in human endothelial cells recapitulated apoptosis, release of pro-inflammatory cytokines/chemokine, and chemotaxis of macrophages22.…”
Section: Discussionmentioning
confidence: 99%
“…miR-10b is expressed in the kidneys of mice, dogs, and cats34. The role of miR-10b in KD is unknown, but a previous report suggested that upregulation of cAMP responsive element binding protein 1 by loss of miR-10b plays an important role in the tumorigenesis of renal cell carcinoma21. Furthermore, miR-10b is significantly downregulated in rejected allografts, and miR-10b inhibition in human endothelial cells recapitulated apoptosis, release of pro-inflammatory cytokines/chemokine, and chemotaxis of macrophages22.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, high expression of CREB1 is associated with metastasis in gastric and breast cancer [25, 26], while knockdown of CREB1 could inhibit liver cancer cell migration [27]. Consistently, CREB1 has also been identified to be highly expressed in glioma tissues and promote cell growth by activating the expression of oncogenic microRNA-23a [28], and plays an important role in the tumorigenesis of renal cancer by loss of tumor suppressive miR-10b-5p and miR-363-3p [29]. However, CREB1 functions like a tumor suppressor in other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…It is specifically located on chromosome 2q31 within the HOXD cluster, between HOXD4 and HOXD8 genes, closer to HOXD4 15. Interestingly, it is reported to be an oncomir in some cancers such as breast cancer,16 gastric cancer,17 hepatocellular carcinoma, glioma18 and lung cancer,19 whereas in other cancers including RCC, miR-10b was reported to have a tumour suppressor role 20 21…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma, miR-10b regulates metastasis and invasion by targeting cell adhesion molecule (CADM) 25. On the other hand, overexpression of miR-10b was shown to inhibit cellular proliferation, migration and invasion in RCC cell lines,21 26 but the exact regulatory mechanisms are not fully understood. Another study reported that loss of miR-10b results in increased expression of the CREB1 oncogene in RCC 21…”
Section: Introductionmentioning
confidence: 99%